2020
DOI: 10.5812/semj.101531
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Empowerment Training Program on the Difficulty of the Transition to Parenthood and Parenting Stress: A Quasi-Experimental Study among Iranian Primiparous Women

Abstract: Background: The process of becoming a mother is one of the most satisfying and fulfilling events in women's lives. Maternity for the first time can be stressful and also can increase anxiety in women. Objectives: The present study aimed to determine the effect of an empowerment training program on the difficulty of transitioning to parenting as well as parenting stress of primiparous mothers. Methods: The sample of this quasi-experimental study consisted of 78 primiparous women who were selected due to conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…37 A home-based quasi-experimental study in Iran demonstrated that follow-up empowerment training by nurses reduced parenting stress and transitioning difficulties such as maternal concerns, changes in life, negative postpartum feelings, and improved enjoyment. 28 Our study shows that home visits are especially impactful for primiparas in low-income settings. Indeed, evidence indicates that young, socio-economically disadvantaged mothers appreciate health visits by professionals as they assist them with recognizing and addressing their needs which can build their agency and thus improve MSE.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…37 A home-based quasi-experimental study in Iran demonstrated that follow-up empowerment training by nurses reduced parenting stress and transitioning difficulties such as maternal concerns, changes in life, negative postpartum feelings, and improved enjoyment. 28 Our study shows that home visits are especially impactful for primiparas in low-income settings. Indeed, evidence indicates that young, socio-economically disadvantaged mothers appreciate health visits by professionals as they assist them with recognizing and addressing their needs which can build their agency and thus improve MSE.…”
Section: Discussionmentioning
confidence: 65%
“…Studies on diverse SE theory-based postdischarge educational interventions demonstrate that they cost-effectively improve primiparous women's maternal outcomes, MSE, with most subsequently improving postnatal outcomes. 21,[25][26][27][28] Evidence favors home-based multimodality programs that incorporate experience, and individualized sessions with key content packages addressing self and baby care with information presented via an array of formats. 5,29 Including self-efficacyenhancing strategies in these programs is critical to improving MSE in adopting health-promoting PNPs There is however a paucity of studies establishing the influence of self-efficacy theory-based multimodality follow-up PNE interventions on MSE among low-income primiparas living in informal settlements.…”
mentioning
confidence: 99%